A potential eco-friendly degradation of methyl orange by water-ball (sodium polyacrylate) stabilized zero valent iron nanoparticles - Saud Bawazeer (Heliyon)
This study presents the synthesis and application of water-ball (sodium polyacrylate) stabilized zero-valent iron nanoparticles (wb@Fe0) for the eco-friendly degradation of Methyl Orange (MO). The nanoparticles were prepared using a chemical reduction method using NaBH4. Characterization techniques including Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Photoelectron Spectroscopy (XPS), and X-ray Diffraction (XRD) were employed to analyze the morphology, elemental composition, valent state and crystallinity of the nanoparticles. The catalytic performance was evaluated under standard conditions, with a maximum degradation efficiency of 94 % achieved for a 0.05 mM MO solution using 10 mg of the catalyst, 0.1 mM NaBH4, at neutral pH and room temperature within 10 min. Optimal degradation occurred at 40 °C and pH 6. The catalyst demonstrated excellent recyclability, maintaining activity over ten reuse cycles. Kinetic studies revealed that the degradation followed first-order kinetics with an R2 value of 0.8907 and a rate constant of 0.3708. Though with a lower R2 value (0.6884), the second-order kinetics model indicated the highest rate constant of 2.6522. Regression and ANOVA analysis confirmed the accuracy of the reaction protocol. This study highlights the potential of water-ball stabilized zero-valent iron nanoparticles for effective dye pollutant removal and degradation, offering a promising approach for environmental remediation.